The Part Of Electronic-Governance In Tax Revenue Collection And Remittance In Nigeria - Oloyede Oloyede; Funmilayo Funmilayo (Universitas Medan Area, 2022)
Governance is all about making life favorable and conducive for the citizens, and in achieving this, the government provides in the state some basic social facilities, such as security of lives and properties, and also put in place infrastructures such as good roads, schools and health services. To achieve these, it is mandatory for the government to generate income in-term of revenue, and this is popularly achieved with taxation. Unfortunately, difficulties arising from tax evasion and corruption limit the power of the government of Nigeria to generate sufficient revenue that is needed. The Government with determination of boosting the level of taxation and its compliance in order to be able to execute its tasks for the citizens, has approved electronic taxation as element of its electronic governance creativity in tune of international performance. Research method that was used for this study was qualitative in nature, secondary data was collected at the review of relevant literatures. The study found out that electronic-taxation has been satisfied to be appropriate in use of tax collection and remittance, and has been proven in calculation-error reduction. It also curtails fraud in the tax offices, eliminates challenges that may arise during reconciliation, and limiting leakages in the tax revenue collected. Electronic taxation through electronic-governance has boosted the volume of revenue generation into the cover of the government, and it saves time and cost. This research paper has recommended that tax officials at the local revenue authority, state internal revenue and the federal inland revenue should shift towards e-taxation, give more enlightenment to the taxpayers on the note of adopting electronic taxation instead of manual processing.